2000
DOI: 10.1381/096089200321643511
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Gastric Bypass, Roux en-Y - 500 Patients: Technique and Results, with 3-60 month follow-up

Abstract: The laparoscopic gastric bypass has been refined over 5 years of use. Though we have not changed the basic operation as we originally described, others have modified the various anastomotic techniques. The weight loss results are very good to excellent, with patients now out to "long-term" follow-up. Resolution of the co-morbidities is documented. The operation has an adequate track record to show effectiveness, and training programs should be established to maximize safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

29
324
2
34

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 783 publications
(395 citation statements)
references
References 7 publications
29
324
2
34
Order By: Relevance
“…While it is possible that the MI faculty had not completely climbed their own learning curves for LRYGB during the early period of fellowship training and that this could represent a bias in the current study, the MI demonstrated CRO for LRYGB comparable to other published benchmark data for cases performed during the period of training [25]. Specifically, the rates of significant complications for the MI, detailed in Table 2, were within the ranges established in landmark publications describing experience with LRYGB [26][27][28]. The MI rate of GJ leak (2.6%) falls within the range of 0-3.6% established in these studies [26][27][28].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…While it is possible that the MI faculty had not completely climbed their own learning curves for LRYGB during the early period of fellowship training and that this could represent a bias in the current study, the MI demonstrated CRO for LRYGB comparable to other published benchmark data for cases performed during the period of training [25]. Specifically, the rates of significant complications for the MI, detailed in Table 2, were within the ranges established in landmark publications describing experience with LRYGB [26][27][28]. The MI rate of GJ leak (2.6%) falls within the range of 0-3.6% established in these studies [26][27][28].…”
Section: Discussionsupporting
confidence: 57%
“…Specifically, the rates of significant complications for the MI, detailed in Table 2, were within the ranges established in landmark publications describing experience with LRYGB [26][27][28]. The MI rate of GJ leak (2.6%) falls within the range of 0-3.6% established in these studies [26][27][28]. Internal hernia occurred in 2.0% of MI patients and in 0.3-3.0% of cases in these studies [27,28].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Lower productivity and higher health care costs resulting from obesity and its comorbidities have led to proposals for governmental intervention [6][7][8][9][10]. Methods for quantifying the costs of obesity costs and the benefits of treatment remain controversial [11][12][13]. Nonetheless, it is well established that about 10% of health care dollars are devoted to obesity treatment, which is economically justified by the increased absenteeism and decreased productivity associated with this disorder [14][15][16][17][18][19].…”
mentioning
confidence: 99%